Climate change - Labrecque, Ellen (Labrecque, Ellen. Global citizens: environmentalism., 2018)
Examines climate change through the lenses of history, geography, civics, and economics. Details large and small ways to stop global warming. Includes tips for using evidence from a variety of sources to form conclusions, color photographs, a glossary, critical thinking questions, and further resources.